RETRACTED: “Recovering With Nature”: A Review of Ecotherapy and Implications for the COVID-19 Pandemic - Chaudhury, Pourabi; Banerjee, Debanjan (Frontiers in Public Health, 2020)
Connection with nature has been considered beneficial for psychological well-being since times of evolution. Differences in Indian and Western thoughts have viewed natural elements in different lights, varying between eco-centrism to anthropocentrism. The intrusion of technology and digitalized lives as a result of globalization has decreased connectedness with nature. Ecotherapy is a novel form of psychotherapeutic technique based on explicit environmental or ecological interventions. Social and therapeutic horticulture, animal-assisted interventions, care farming, green exercise, environmental conservation and wilderness therapy are some of the ecosystem-based approaches used in mental health. Based on the principles of positive and client-centered psychology, ecotherapy-related techniques have been shown to be effective in medical disorders like hypertension, obesity, post-surgical recovery and psychosocial conditions like depression, stress reduction, post-traumatic stress disorder (PTSD), attention deficit hyperkinetic disorder (ADHD) and adjustment disorders. The principles of ecotherapy have been integrated into other psychotherapeutic techniques for better efficacy. This review attempts provides an overview of techniques, applications and challenges related to ecotherapy in psychology. The implications of its use during the ongoing Coronavirus 2019 (COVID-19) crisis, social isolation and consequent psychosocial aftermath are also discussed.